2011
DOI: 10.1016/j.fct.2010.05.081
|View full text |Cite
|
Sign up to set email alerts
|

Konzo outbreak among refugees from Central African Republic in Eastern region, Cameroon

Abstract: Konzo is a spastic paraparesis of sudden onset, linked to the exclusive consumption of insufficiently processed bitter cassava as staple food combined with low protein intake. Around 60,000 refugees from the Central African Republic sought refuge in villages in eastern Cameroon between 2005 and 2007. Médecins Sans Frontières was providing nutritional and medical assistance in the villages affected by displacement. We describe cases of konzo seen at the mobile clinics organized in these villages. Basic informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 5 publications
(5 reference statements)
1
31
0
1
Order By: Relevance
“…Importantly, they were more resistant to predation by monkeys and wild pigs (Cliff et al 1997), as noted earlier by Cock (1982). More recently, konzo associated with war has been reported from the Democratic Republic of Congo (Chabwine et al 2009) and among war refugees from Central African Republic in Cameroon (Ciglenecki et al 2009). These latter examples show that when social catastrophes limit people's options, maniocrelated public health problems can develop even in regions with long and successful experience in adapting to highcyanogen varieties of the crop.…”
Section: Management Of Nutrients For Crop Growthmentioning
confidence: 62%
“…Importantly, they were more resistant to predation by monkeys and wild pigs (Cliff et al 1997), as noted earlier by Cock (1982). More recently, konzo associated with war has been reported from the Democratic Republic of Congo (Chabwine et al 2009) and among war refugees from Central African Republic in Cameroon (Ciglenecki et al 2009). These latter examples show that when social catastrophes limit people's options, maniocrelated public health problems can develop even in regions with long and successful experience in adapting to highcyanogen varieties of the crop.…”
Section: Management Of Nutrients For Crop Growthmentioning
confidence: 62%
“…In contrast to TAN and MNCPD, konzo still occurs in sub-Saharan Africa [8][12]. We recently showed that older children, females, and those undernourished were at higher risk for motor and cognitive deficits among populations that rely almost exclusively on cassava as staple diet [9], [13].…”
Section: Introductionmentioning
confidence: 99%
“…Years of occurrence of all konzo epidemics in the past century in DR Congo (Trolli, 1939;Vileu, 1942;Lucasse, 1952;World Health Organisation, 1982;Tylleskar et al, 1991;Bonmarin et al, 2002;Chabwine et al, 2011), Mozambique (Ministry of Health Mozambique, 1984Cliff, 1994;Ernesto et al, 2002;Cliff et al, 2011), Tanzania (Howlett et al, 1990(Howlett et al, , 1992Mlingi et al, 2011), and Central African Republic (Ciglenecki et al, 2011) were obtained from published studies. Cycle plots of ENSO and PDO timeseries from 1915 to 2014 were drawn to show the warm and cold phases.…”
Section: Konzo Epidemics Datamentioning
confidence: 99%
“…Disabling spastic paraparesis is the residual deficit in most subjects (Ministry of Health Mozambique, 1984). Major konzo epidemics occurred during severe droughts from the late 1920s to late 1940s (Trolli, 1939;Vileu, 1942;Lucasse, 1952), and from the late 1970s to early 2000s (World Health Organisation, 1982;Ministry of Health Mozambique, 1984;Tylleskar et al, 1991;Ciglenecki et al, 2011;Mlingi et al, 2011). Interannual konzo cases occurred, however, between epidemics (Tylleskar et al, 1991;Cliff, 1994).…”
Section: Introductionmentioning
confidence: 99%